Mobilização precoce no cuidado intensivo: indicadores de qualidade após implementação de um programa multiprofissional, conhecimentos e práticas fisioterapêuticas no contexto pandêmico nacional e nova proposta de intervenção motora para pacientes comatosos críticos - Biazon, Thaís Marina Pires de Campos (2021)
The material of this thesis is composed of three studies that deal with a common theme, motor rehabilitation in the intensive care unit (ICU) applied through early mobilization (EM) as shown below. The EM was able to promote positive effects on intensive care quality indicators in economically developed countries where resources and other facilitators are more available. However, there is no evidence of these effects in countries of medium to low economic development. Therefore, the first study of this thesis was designed with the objective of investigating the effects of the multiprofessional implementation of EM on indicators of quality of intensive care in Brazil. EM results in a reduction of intensive care unit acquired atrophy (ICUAA) with benefits for the reduction of mortality. However, there is no information about this knowledge on the part of intensive care physiotherapists and on their clinical practices and barriers to motor therapies for reducing ICUAA in critically comatose patients with COVID-19 in Brazil. Thus, the second study of this thesis was developed aiming to investigate the knowledge and practices of intensive care physiotherapists and the barriers to such therapies in this type of patient. Finally, ICUAA and intensive care unit acquired weakness (ICUAW) are associated with high mortality, reduced physical function and quality of life. The blood flow restriction (BFR) method associated with passive mobilization (PM) (BFRp) was able to reduce ICUAA in comatose patients and BFR associated with the neuromuscular electrical stimulation (NMES) to increase muscle mass in patients with spinal cord injury. Despite this, BFR can promote unknown repercussions on the cardiovascular system of critically comatose patients. Therefore, the third study of this thesis was proposed with the aim of describing a pilot study protocol for a randomized and controlled clinical trial that allows investigating the effect of BFRp and BFRp combined with NMES (BFRpE) on cardiovascular safety and applicability and on neuromuscular adaptations, physical function and quality of life of critically comatose patients. The results of these studies may contribute to the advancement of the practice of rehabilitation in intensive care, strengthening the evidence of motor rehabilitation as a health strategy, reducing conceptual barriers for the implementation of intensive rehabilitation in environments with few financial and material resources and, therefore, contribute to the call by the World Health Organization to improve global motor rehabilitation (Rehabilitation 2030: A Call for Action).